Analysis of marketing strategy of technology enterprises based on swot model: Taking Apple and Huawei as examples - Liu Yuying (SHS Web of Conferences)
In August 2018, Apple achieved a significant milestone by becoming the first company in history to be valued at $1 trillion. Two years later, in August 2020, Apple once again made headlines by reaching an unprecedented market value of $2 trillion, solidifying its position as a global leader in the technology industry and setting new benchmarks for corporate valuation. Apple, the digital technology giant, has been increasing in value by and large every year. What is the marketing strategy behind this, and why is Apple so far ahead of other digital technology companies. Based on swot model, the comparative analysis method is adopted to compare Apple and Huawei. Analyze their internal and external factors through advantages and disadvantages, opportunities and threats, and then put forward corresponding suggestions for the improvement of the two companies. In addition, the two companies also found different pricing models and ways to promote products through different channels. Research finding Huawei and Apple are different in the design of product appearance, Apple has a complete ecosystem, and has a strong brand image and loyalty, they both have a strong supply chain management and can ensure the user experience first.It is also found that Huawei attaches great importance to employees and can make good use of employees in different technical levels, thus forming a strong R&D team with strong independent innovation ability and strong 5G technology.